Find the equation of a straight line passing through the point (0,1) which is perpendicular to the line y=-2x+2
Find the equation of a straight line passing through the - 1

Answers

Answer 1
Answer:

Answer:

y = (1)/(2) x + 1

Step-by-step explanation:

The equation of a line in slope- intercept form is

y = mx + c ( m is the slope and c the y- intercept )

y = - 2x + 2 ← is in slope- intercept form

with slope m = - 2

Given a line with slope m then the slope of a line perpendicular to it is

m_(perpendicular) = - (1)/(m) = - (1)/(-2) = (1)/(2)

The line crosses the y- axis at (0, 1) ⇒ c = 1 , then

y = (1)/(2) x + 1 ← equation of perpendicular line


Related Questions

I don't understand how to do this math problem, help me?
Please help me asap ..
If the circumference is 34.54 units what is the radius
Find the missing number 1:2 = 3: ____        A. 1   B. 2   C. 6   D. 3
Evaluate [3(5 + 6) + 2] ÷ 7

The Ferris Wheel makes 12 revolutions per ride. How far would someone travel during one ride?

Answers

Answer:

C=12{*}{\pi}{*}d.

Step-by-step explanation:

It is given that The Ferris Wheel makes 12 revolutions per ride.

Now, The circumference to find the distance a rider travels in 1 revolution is given as: C={\pi}d where "d" is the diameter.

For 12 revolutions, the distance a rider travels is given as: C=12{*}{\pi}{*}d.

1 revolution = the circumference of the wheel = (pi) x (diameter) .

12 revolutions = 12 x the circumference of the wheel = (12) x (pi) x (diameter) .



Simplify a - {b - [c - (d - e) - f] - g}.a + b + c - d + e - f + g
a - b + c - d + e - f + g
a + b + c + d + e - f + g
a - b + c - d + e + f - g

Answers

Answer:

a - b + c - d + e - f + g

Step-by-step explanation:

We know that,

(-)(-) = (+),

(-)(+) = (-),

(+)(-) = (-)

(+)(+)=(+)

Now,

Here, the given expression is,

a - \{b - [c - (d - e) - f] - g\}

a-\{b-[c-d+e-f]-g\}

a-\{b-c+d-e+f-g\}

a-b+c-d+e-f+g

Hence, Second option is correct.

 a - {b - [c - (d - e) - f] - g} 
= a - {b - [c - d + e - f] - g} 
= a - {b - c + d - e + f - g} 
= a - b + c - d + e - f + g.
so ur answer is the third one C there all equivalent so the last one is the answer choice so there u go

21x^3 + 6x^2 - 28x - 8 factor this expression with work please?

Answers

21x^3 + 6x^2 - 28x - 8 \n \n 3x^2 (7x + 2) - 4(7x + 2) \n \n (7x + 2)(3x^2 - 4) \n \n

The final result is: (7x + 2)(3x² - 4).
21x^3+6x^2-28x-8
(21x^3+6x^2)-(28X+8)
3x^2(7x+2)-4(7x+2)
3x^2-4=0 and 7x+2=0

Suppose you know three minimum,lower quartile,median, upper quartile, and maximum values for a set of data. Explain how to create a box plot for the set of data.

Answers

Answer: First, draw and label a number line. Then plot the five values that are given above the line. Draw a box from the lower quartile to the upper quartile, with a line dividing it at the median. Then draw lines from the minimum and maximum values connecting to the box to form the whiskers.

Answer:

Create a number line and label it.

Above the number line, plot the five values.

Draw a box from the lower quartile to the upper quartile.

Divide the box at the median.

Connect the minimum and maximum values to the box.

Step-by-step explanation:

edg2020

Write an equation in slope-intercept form of the line through point P(6, –1) with slope 4.A. y = 4x – 25
B. y = 4x – 1
C. y + 1 = 4(x – 6)
D. y + 6 = 4(x – 1)

Answers

Answer:

The answer is the option A

y=4x-25

Step-by-step explanation:

we know that

The equation of the line into slope-intercept form is equal to

y=mx+b

where

m is the slope

b is the y-coordinate of the y-intercept of the line

In this problem we have

m=4

point(6,-1)

substitute the values in the equation and solve for b

-1=4*6+b

b=-1-24=-25

The equation of the line is equal to

y=4x-25


y = mx+b

m= 4 

y= 4x+b

solve for b using (6,-1)

-1 = 4 (-1)+b
b=3

therefore equation is y=4x+3

same as (y+1)=4(x-6)

Find the slope of the line on the graph

Answers

Answer:

m =1/2

Step-by-step explanation:

Use two points on the line given.

(0 , 2) & (-4 , 0)

You are solving for the slope. The slope formula:

m (slope) = (y₂ - y₁)/(x₂ - x₁)

Let:

(x₁ , y₁) = (-4 , 0)

(x₂ , y₂) = (0 , 2)

Plug in the corresponding numbers to the corresponding variables:

m = (2 - 0)/(0 - (-4))

Simplify:

m = (2)/( 0 - (-4))

m = (2)/(0 + 4)

m = 2/4

Simplify the slope. Divide the common factor 2 from both the numerator and denominator:

m = (2/4)/(2/2) = 1/2

1/2 is your slope.

~

Answer:

0.5

Step-by-step explanation:

the rise is 4 and the run is 8 so it would be 4/8 or 1/2 which would equal 0.5